THE IMPACT OF OWNERSHIP STRUCTURE AND CORPORATE GOVERNANCE ON PROFITABILITY AND FIRM VALUE - Gabriella Joanne; Melinda Haryanto (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2019)
This research aims to analyze the impact of ownership structure and corporate governance on profitability and firm value. The profitability and firm value, which are the dependent variables in this study, will be calculated using ROA (Return on Assets) and Tobin’s Q. Ownership structure and corporate governance as the independent variables consist of institutional and government ownership, board size, independent board member, and type of auditor with size of firm, debt ratio, dividends yield, and age of company as the control variables. The samples that are used in this research are the 24 consumer goods industry companies that are listed in the Indonesia Stock Exchange. The technique that is used in this research is multiple regression analysis. The result of this research shows that there is a significant positive influence of type of auditor on ROA (Return on Assets) and Tobin’s Q. Moreover, institutional ownership and board size has a negative significant influence on ROA and Tobin’s Q. While, government ownership and independent board member has a negative but insignificant impact on ROA and Tobin’s Q.